Early Sensory Contributions to Contextual Encoding Deficits in Schizophrenia - Dias, Elisa C. (Arch Gen Psychiatry, 2011)
1. CONTEXT: The “AX”-version of the visual continuous performance task (AX-CPT) is widely used for investigating visual working memory dysfunction in schizophrenia. Event-related potentials (ERP) provide an objective index of brain function, and can be used to evaluate brain substrates underlying impaired cognition in schizophrenia. 2. OBJECTIVE: To assess mechanisms underlying visual working memory dysfunction in schizophrenia relative to impairment of early visual processing. 3. DESIGN, SETTING AND PARTICIPANTS: Between-group design in a chronic treatment setting, with 30 individuals with schizophrenia and 17 healthy comparison subjects. Three versions of AX-CPT, with parametric variations of the proportions of trial types, were used to test performance and underlying neural activity under differential challenge situations. Contrast sensitivity measures were obtained from the majority of subjects. 7. MAIN OUTCOME MEASURES: Behavioral performance was assessed using d’-context scores. Integrity of stimulus- and task-related cortical activation to both cue and probe stimuli was assessed using sensory (C1, P1, N1) and cognitive (N2, CNV) ERP components. Early magnocellular/parvocellular function was assessed using contrast sensitivity. Linear regression and path analyses were used to assess relations between physiological and behavioral parameters. 8. RESULTS: Patients showed reduced amplitude of both early sensory (P1, N1) and later cognitive (N2, CNV) ERP components. Deficits in sensory (N1) and cognitive (N2) components to cue stimuli contributed independently to impaired behavioral performance. In addition, sensory deficits predicted impaired cognitive ERP generation. Finally, deficits in performance correlated with impairments in contrast sensitivity to low, but not high, spatial frequency stimuli. 9. CONCLUSIONS: Working memory deficits in schizophrenia have increasingly been attributed to impairments in stimulus encoding, rather than to failures in memory retention. The present study provides objective physiological support for encoding hypotheses. Further, deficits in sensory processing contribute significantly to impaired working memory performance, consistent with generalized neurochemical models of schizophrenia.